Streptococcus pyogenes: phenomenon of nonimmune binding of human immunoglobulins and its role in pathology - L. A. Burova; A. N. Suvorov; A. A. Totolian (Медицинская иммунология, 2022)
M and M-like proteins represent the main pathogenicity factors of Streptococcus pyogenes, a widely spread and potentially lethal bacterial pathogen. These proteins provide resistance of the microbe to innate and adaptive immune response, due to attraction of specific human proteins to the streptococcal surface. Nonimmune binding of immunoglobulins G (IgG) and A (IgA) via their Fc domains to M and M-like proteins was described over 40 years ago, but its role for the pathogenicity of Streptococcus pyogenes is far from definite resolution. The discovery of this phenomenon should be considered among quite significant achievements of modern microbiology, since it had a huge impact upon development of innovative approaches, technologies and tools for microbiological, immunological and molecular diagnostics. It also promoted fundamental studies in pathogenesis of distinct infectious states and their complications caused by S. pyogenes. The non-immune binding of host immunoglobulins was previously suggested to be important mainly in immune conditions on the surface of mucous membranes and their secretions, but not in blood plasma, whereas other studies have pointed to significance of this phenomenon in protecting microbes from phagocytosis in non-immune blood of the host. It was also shown that the effect of Fc-binding causes increased pathogenicity of streptococci both in primary focus of infection, and during chronical course of the process, thus contributing to development of autoimmune diseases caused by S. pyogenes infection and leading to tissue damage in experimental animals. The experimental autoimmune process can be prevented by administering purified Fc fragments of immunoglobulins to the animals, blocking this process at the early stages of its development. A significant place in pathogenesis of IgA nephropathy (IgAN) belongs to streptococcal diseases. IgAN has been described as a mesangial proliferative process, due to initial IgA-Fcα deposition in renal mesangium cells. The data from literature describe successful modeling of individual IgAN traits, and expand our understanding of pathogenic properties and functions of Fcα binding receptor M proteins of S. pyogenes. The data reviewed in the article also presume the relevance of recently proposed ideas about an important role of non-immune Ig binding in streptococcal diseases, even in cases that differ in their development mechanism. These studies, including possible search for tools and techniques of preventive and potentially therapeutic applications, require additional efforts to study the binding of Fc fragments of IgG and IgA to M and M-like proteins of Streptococcus pyogenes.